Penentuan Rute dan Stasiun Transportasi Trem di Kecamatan Somba Opu, Kabupaten Gowa - Afifah Nabila; Arifuddin Akil; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Based on the general plan for the development of land transportation in 2015-2035, the Indonesian Ministry of Transportation has a direction for the development of urban mass public transportation in order to support movement between centers of activity and the provision of reliable and competitive transportation services. This study aims to identify the most influential factors in the consideration of determining routes and stations, determine potential tram routes, and determine the location of potential tram stations in Somba Opu Subdistrict. This research was carried out from October 2019 until April 2020, located in Somba Opu District, Gowa Regency. This research is a descriptive study, with quantitative and qualitative approaches. The analysis techniques used in this study were expert choice analysis, MAT and spatial analysis (desire line, network analyst, overlay, and grid-based. The results of this study indicate that: 1) The priority factors in determining the route are road network characteristics, community movement patterns, the distribution of activity centers, land use, and population distribution, while in determining the location of the station the priority criteria are close to the location of the generator. , location of attraction, as well as intermodal integration considerations; 2) The tram route of Somba Opu Subdistrict passes arterial and collector roads (Jl. Sultan Hasanuddin - Jl. Andi Mallombasang - Jl. Poros Malino); 3) The potential location to become a station location is the grid which has a value of 86% -100% (very potential). The tram station is located on Jl. Andi Mallombasang, Sungguminasa Village.